Games: an opportunity that we must seize - Calderón-Rehecho, Andoni (Anuario ThinkEPI, 2015)
A literature review revealed that games offer many advantages that games have for learning, developing skills, being creative, solving problems, interacting... In addition, games are a great opportunity for the library and information worlds, particularly for information literacy, that should not be missed. Their importance has been known for many years, but more recently they are being revalued with the current trend of gamification, i.e, the application of games to make various activities more enjoyable and more effective, especially training activities. The new technologies have enabled the development of video games that add much more value to gaming, such as the possibility of assessing and ranking our skills.
Keywords: Games; Video games; Advantages; Gamification; Education; Learning; Literature review.